Electrical Properties of Indium doped Alumina (Al2O3) Thin Films - Hadaate Ullah; Shahin Mahmud (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
To know the electrical properties of any materials is very important for practical application of that material. In this paper I have tried to find out the proper electrical properties of Indium doped Alumina (Al2O3) for practical application of this Alumina. For this purpose all thin films are deposited on glass substrate by electron beam evaporation technique at a pressure of about 1.5 x 10-6 torr and at temperature of 307K. The thickness of Indium doped Al2O3 films (25%w, 30%w and 40% w of In2O3) range from 68 nm to 183 nm. For 25% In2O3 doped alumina the conductivity at room temperature is 24.10mho/cm, for 30% In2O3 doped alumina this value is 82.99mho/cm and for 40% In2O3 doped alumina this is 129.10mho/cm. The resistivity and sheet resistance decrease with the increase of doping concentration that means the conductivity increases with doping concentration. DOI: http://dx.doi.org/10.11591/telkomnika.v14i2.7747